2014
DOI: 10.1111/eos.12143
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of reporting suspicions of child maltreatment in pediatric dentistry

Abstract: This study examined the factors that lead specialists in pediatric dentistry to suspect child abuse or neglect and the considerations that influence the decision to report these suspicions to social services. Focus group discussions were used to identify new aspects of child maltreatment suspicion and reporting. Such discussions illuminate the diversity of informants' experiences, opinions, and reflections. Focus groups included 19 specialists and postgraduate students in pediatric dentistry. We conducted vide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 36 publications
2
39
0
Order By: Relevance
“…The decrease in incidence after 2011 may have different causes. Studies describe a lack of continuous education, lack of cooperation with the social services, and previous negative experiences with reporting as reasons for not reporting . Wiklund found that collaboration with the social services leads to fewer reports, in contrast to what might be expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in incidence after 2011 may have different causes. Studies describe a lack of continuous education, lack of cooperation with the social services, and previous negative experiences with reporting as reasons for not reporting . Wiklund found that collaboration with the social services leads to fewer reports, in contrast to what might be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Also, dental professionals may have had already referred the most vulnerable children in their caseload, and thereafter identified fewer new cases. Furthermore, there is a well‐known difficulty in differentiating dental caries from dental neglect …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29][30][31] The challenges dental health personnel experience when suspecting child maltreatment and deciding whether to report to CWS may be related to difficulties making decisions under uncertainty. [32] More specifically, signs of child maltreatment are often unclear and ambiguous and the consequences of reporting to CWS are often unclear. According to Baumann et al, [33] decisions made under uncertainty in CWS are best understood within a decision-making ecology model.…”
Section: Introductionmentioning
confidence: 99%
“…Even among paediatric dentists, a gap is evident between 67% ever having recognised and 29% ever having referred concerns 54. These gaps reflect dentists’ dilemmas about their contradictory roles of supporting or reporting families, differentiating compromised well-being from significant maltreatment and perceived shortcomings of the child protection system 62. Lessons learnt in a number of SCRs indicate that harm might have been avoided had dental professionals raised concerns earlier.…”
Section: Dentists As Contributors To Safeguarding Childrenmentioning
confidence: 99%